Deepening Root Inputs Potential Soil Carbon Accrual From Breeding for Deeper Rooted Maize - Cotrufo, M Francesca (Global change biology, 2024)
© 2024 The Author(s). Global Change Biology published by John Wiley & Sons Ltd.